Karnataka Annual Plan 1980-81 Volume-V District Plans Sectorwise Programmes - Planning Commission (Planning Commission, 1980)
A major effort in achieving the objective of full employment would be to formulate area specific plans at the grass roots level. For realising this goal, Karnataka Government have brought about a fundamental change in the planning process by introducing two-tier planning process beginning from 1978-79. State Plan Schemes are bifurcated into District Sector and State Sector Schemes based on the criterion whether a particular scheme is of direct benefit to a district or not. 75 per cent of State Plan outlays, after taking out the outlays on State Sector Schemes and indivisible items, are distributed to districts on the basis of objective criteria.
Government of Karnataka